Dietary arginine silicate inositol complex increased bone healing: histologic and histomorphometric study - Yaman, Ferhan; Acikan, Izzet; Dundar, Serkan; Simsek, Sercan; Gul, Mehmet; Ozercan, Ibrahim Hanifi; Şahin, Kazım (Dove Medical Press Ltd, 2016)
Background: Arginine silicate inositol complex (ASI; arginine 49.5%, silicon 8.2%, and inositol 25%) is a novel material that is a bioavailable source of silicon and arginine. ASI offers potential benefits for vascular and bone health. Objective: The aim of this study was to evaluate the potential effects of ASI complex on bone healing of critical-sized defects in rats. Methods: The rats were randomly assigned to two groups of 21 rats each. The control group was fed a standard diet for 12 weeks; after the first 8 weeks, a calvarial critical-sized defect was created, and the rats were sacrificed 7, 14, and 28 days later. The ASI group was fed a diet containing 1.81 g/kg of ASI for 12 weeks; after the first 8 weeks, a calvarial critical-sized defect was created, and the rats were sacrificed 7, 14, and 28 days later. The calvarial bones of all the rats were then harvested for evaluation. Results: Osteoblasts and osteoclasts were detected at higher levels in the ASI group compared with the control group at days 7, 14, and 28 of the calvarial defect (P<0.05). New bone formation was detected at higher levels in the ASI group compared with the controls at day 28 (P<0.05). However, new bone formation was not detected at days 7 and 14 in both the groups (P>0.05). Conclusion: ASI supplementation significantly improved bone tissue healing in rats with critical-sized defects. This study demonstrated that ASI can enhance bone repair and has potential as a therapeutic regimen in humans.
Keywords: arginine silicate inositol; bone healing; osteoblast; osteoclast; critical-sized defect